KEMAMPUAN KOGNITIF FISIKA SISWA MELALUI PEMBELAJARAN MENGGUNAKAN LKS BERBASIS JELAJAH ALAM SEKITAR (JAS) PADA MATERI POKOK SUHU DAN KALOR DI SMA N 2 XIII KOTO KAMPAR - Jusi Putri Ardini Putri Ardini; Azhar Azhar '; M. Nor M. Nor ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research aims at describe the cognitive abilities of physics through the use of learning-based LKS Natural (JAS) in the subject matter and the temperature of the heat in SMA N 2 XIII Koto Kampar and know the difference between the cognitive abilities of students studying physics using worksheets based natural learning (JAS ) with students who learn using conventional LKS. This research was conducted in SMA N 2 XIII Koto Kampar in February to June 2015. The subjects were class X IPA1 and X IPA2 totaling 49 students who have been tested for normality and homogeneity of both classes. The design of this study was pre-experimental design with Intact-Group Comparison. The research instrument used is the achievement test of cognitive ability. Data collection techniques is the provision of learning outcomes of cognitive ability tests consist of 20 multiple choice items. Data were analyzed through descriptive and inferential analysis. Descriptive analysis of the results obtained by the average absorption using LKS JAS class higher than the class that uses conventional LKS both categories, the effectiveness of otherwise effective learning, mastery learning students in classical declared complete mastery of the subject matter and declared incomplete. Inferential analysis through the calculation of statistical values t test manually and through SPSS 17 obtained tcount = 1.282, while ttable = 2.012. Based on the criteria of hypothesis testing tcount <ttable (1.282 <2.012), so there is no significant difference between Cognitive Ability Physics students learn to use worksheets based natural learning (JAS) with students who learn using conventional LKS.Key Words: Cognitive Ability, Nature-Based Learning (JAS), Temperature and Heat